Kepatuhan Penerapan Alat Pelindung Diri (APD) Pada Pekerja Konstruksi - Cynthia Nafista (Universitas Airlangga, 2022)
Background: The number of work accidents in developing countries such as Indonesia is known to be 4 times higher than industrial countries. The high number of accidents can occur due to the low level of education of workers and minimal work experience, causing unsafe human acts. Personal Protective Equipment is an important component in preventing work accidents for workers, especially in the field of construction services. However, the awareness of construction project workers on the importance of using PPE in Indonesia is still low because the average worker still has a relatively low level of education and minimal work experience. Objectives: This study aims to analyze the relationship between level of education and work experience with obedience in using Personal Protective Equipment (PPE) on construction workers. Methods: This research is an observational study with a cross sectional design. This study used total sampling as the population and the research sample as many as 62 workers. Results: The results of the analysis show that the correlation coefficient at the level of education is -0.191 with a negative direction and the coefficient of work experience is 0.068 with a positive direction, which means that there is a very weak relationship between the variables of education level and work experience of workers with compliance with using PPE. Conclusions: The higher the level of education does not mean compliance in using Personal Protective Equipment (PPE) is higher and the longer the working period of the worker does not mean the level of compliance in using Personal Protective Equipment (PPE) is higher.